Pengaruh Kepemimpinan Kepala Desa terhadap Kesejahteraan Masyarakat Desa Mojosari Kecamatan Mantup Kabupaten Lamongan - Sofia Tri Septiawati; Imam Syafi’i (Journal of Economics, Management, and Accounting, 2025)
This study aims to examine the influence of village head leadership on community welfare in Mojosari Village, Mantup District, Lamongan Regency. The approach used is a quantitative method with data collection techniques through the distribution of questionnaires to 50 respondents. The research instrument has undergone validity and reliability tests, with results showing that all statement items are valid and have a Cronbach’s Alpha value of 0.852, indicating a high level of reliability. Correlation analysis results show an R value of 0.113, which is lower than the r-table value of 0.3281, and an R Square value of 0.013. These findings indicate that village head leadership has an effect on community welfare, but this influence is not statistically significant, contributing only 1.3%, while the remaining 98.7% is influenced by factors outside the research model. Thus, it can be concluded that village head leadership plays a role in improving community welfare, but its influence is still considered weak and not significant, so other variables are needed, such as community participation, village development policies, and the role of social institutions, to strengthen the research model and provide a more comprehensive understanding of the factors that affect the welfare of village communities.